Shaping Techniques in Islamic Guidance Counseling to Overcome Teenagers Who Neglect Prayer - Hanafi, Hanafi; Saimun, Saimun; Irmayani, Amalia Putri (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research is motivated by behavior that does not pay attention to the moral values contained in every action carried out. This problem was carried out by teenagers in Selojan Hamlet. It is known that teenagers in Selojan Hamlet like to neglect prayer because of influences from within the individual and also influences from the environment in the form of the family environment and then the influence of peers so that this neglect of prayer occurs and is carried out by teenagers in Selojan Hamlet which gives rise to negative factors. for victims/perpetrator. The objectives of this research are: (1) to determine the factors that influence teenagers who neglect prayer; (2) to find out the process of Islamic guidance and counseling using shaping techniques in dealing with teenagers who neglect prayers in Selojan Hamlet, Karang Sidemen, Central Lombok Regency. This type of researcher uses qualitative research methods to discuss adolescent problems in Selojan Hamlet. Research data was obtained through observation, interviews and documentation. The types and sources of data used are primary and secondary data. The data analysis techniques used are data reduction, data presentation and drawing conclusions. Meanwhile, checking the validity of the data used is triangulation of sources and triangulation of methods. The results of the research show: factors that influence teenagers who neglect prayer include: (1), internal factors include: a). Lazy; b). Busy; c). Fatigue. The two external factors include: family environment, education, friends, technology and online games. (2). The process of Islamic counseling guidance with shaping techniques in dealing with teenagers who neglect prayer, namely first, problem identification, diagnosis, prognosis, therapy and evaluation. .